Wielka Gra” na Oceanie Indyjskim. Chiny, Indie i Stany Zjednoczone w regionalnej rywalizacji mocarstw - Karczewski, Maciej (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
The Indian Ocean constitutes an area which is rich in resources and vital to shipping. In this region there are some strategic sealines that enable communication of China and India with this resourceful area. Due to the fact that the Indian Ocean region is rich in oil, China and India seek dominance in this part of the world. The article explains and describes the dynamic of greatpower rivalry in various aspects. It also analyzes the role of the Unites States as stabilizing power in the new political and economic environment in Asia.